Influence of Humic Acid on the Strength of Cement-Soil and Analysis of Its Microscopic Mechanism - Jing Cao; Fangyi Liu; Siyang Huang; Cheng Kong; Huafeng Sun; Yue Gao; Fuhua Liu; Jianyun Li; Guoshou Liu (Advances in Civil Engineering)
The disposal of soil containing humic acid (HA) poses an increasingly difficult problem for geotechnical environmental engineering. In this study, the unconfined compressive strength (UCS) test of cement-soil with different HA contents is conducted to analyze the effect of HA on the strength of cement-soil. Mercury intrusion porosimetry (MIP), scanning electron microscopy (SEM), and X-ray diffraction (XRD) experiments reveal the effective mechanism of HA on the strength of cement-soil from the microscopic level. The results show that the strength of cement-soil decreases gradually with the increase of HA content. The failure mode of cement-soil slightly changed from brittle failure to plastic failure. The microscopic test shows that the incorporation of HA will lead to the apparent enlargement of the pores in the cement-soil. The large pores in the sample increase, the small micropores decrease, and the structure tends to be loose and overhead. The increased HA content added will significantly reduce the cement hydration products and destroy the cementation of the hydration products.